(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , GHf TGcQ J (B764 (3g` s
(3ChdgG (B:s
(3MhGOK SfI NeS hCQHYjf hSJeGFI s
(3BNQgG (B:s
(3Edi SfI SHYjf hSJeGFI s
(3GdLRA GdKGdK YTQ ef GdfSNI faSgGs
(3heceJhH YdjgG Gfg(B: (3GdLRA GdYTQhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B1185s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B48 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B48 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B297 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs